Shelf-life extension of pasteurised and ready-to-eat foods by hyperbaric storage at room temperature - Lemos, Álvaro Tomaz de (2022)
Recently, food preservation by hyperbaric storage (HS) at room temperature (RT) has been pointed as an alternative/complement to refrigeration (RF). So, the aim of this work was the evaluation of HS/RT (25-100 MPₐ) on shelf-life extension of a high pressure pasteurised milk and on a ready-to-eat fish soup comparatively with RF. Moreover, the use of moderate pressures (125-250 MPₐ) at RT was studied, for the first time, as a new nonthermal pasteurisation methodology. In this sense, microbiological and physicochemical analyses, including a sensorial analysis. According to the results, during HS/RT occurred growth inhibition of endogenous microorganisms at 50 MPₐ, while above 75 MPₐ was verified microbial inactivation, with this latter effect increasing with pressure. Concerning inoculated microorganisms, Escherichia coli, Listeria innocua and Salmonella Senftenberg, HS/RT (75 e 100 MPₐ) progressively reduced their values to below the detection limit, differently of RF. Globally, the physicochemical parameters analysed were not affected by HS/RT or were affected in the same manner as with RF, as pH, total soluble solids and colour. On milk, HS/RT increased slightly the apparent viscosity, secondary lipid oxidation and soluble protein content compared to RF. The fatty acids profile and the metabolic profile analysed by NMR were similar between HS/RT and RF. Furthermore, the multivariate analysis showed that the storage time had more impact on milk metabolites than the different storage pressures. The volatile organic profile was similar between HS/RT (75 and 100 MPₐ) and RF, and no deteriorative compounds were observed, except for 40 and 60 days at 50 MPₐ (ethanol and acetoin) due to the microbial growth. On fish soup sensorial analysis revealed that fresh samples were preferred in relation to samples stored at HS/RT (75 MPₐ) and RF, both at 14 days, pointing the colour and aroma as the main differentiate factors, while 75 MPₐ and RF samples presented similar scores. With use of moderate pressures (125-250 MPₐ) was possible to reduce more than 5.0 logarithmic units of the inoculated microorganisms mentioned above, being proposed a new nonthermal pasteurisation method called “moderate pressure pasteurisation” (MPP). Thus, HS/RT showed to be a feasible alternative/complement to RF to extend shelf-life of both foods studied, with much less energetic consumption and carbon footprint, since it only needs energy during the compression phase and not to keep the low temperature as occurred in RF. Additionally, MPP showed potential as a nonthermal pasteurisation methodology that can be carried out at the same time foods are being preserved at RT, being quasi energetically costless.